Legal Reformulation of Ultra-Micro Financing as an Instrument for Strengthening the People's Economy in Indonesia - Tambunan, Melpa; Prasetyo, Dedy Ardian; Patarawadee, Patarawadee (Journal Evidence Of Law, 2025)
Ultra Microfinance (UMi) is one of the inclusive strategies to encourage people's economic growth, especially for small businesses that have not been reached by the formal financial system. However, the implementation of this program still faces obstacles due to the lack of comprehensive and responsive legal regulations. This research aims to analyze the gap between legal norms and the practice of ultra-micro financing implementation in the field and offer an adaptive and equitable legal reformulation model. Using a juridical-normative and empirical approach, data was collected through a literature study, interviews with micro business actors, and focus group discussions (FGDs) with lending institutions and stakeholders. The results show that the lack of legal protection, regulatory incoherence, and low legal literacy of the community hinder the effectiveness of the UMi program. Therefore, regulatory reformulation is needed in the form of a master legal framework that includes clear legal substance, strong institutional structure, and participatory legal culture. This research offers a conceptual model of legal reformulation of ultra-micro financing based on the principles of distributive justice, financial inclusion, and legal responsiveness. The results are expected to provide conceptual and practical contributions in the development of financing law policies that favor the community and support inclusive and sustainable national economic development.